Analysis of Qur'anic Discourse in The Light of Modern Linguistic Studies | تحليل الخطاب القرآني في ضوء الدراسات اللسانية الحديثة - Naous Benyahia (Al-Zahra : Journal for Islamic and Arabic Studies, 2021)
It is no secret that the Qur'anic discourse is divine, and no one has been able to call it except as God called it in his Holy Book, where he called it (the book) unique from other speeches and in all his levels of sound, lexical, compositional, rhythmic, and deliberative. This research employs the descriptive analytical approach to investigate the latest linguistic studies, which is the science of the text, which is the “linguistics of the text” in order to find out the aspects of its coherence, consistency and consistency. Among the objectives of this research are: To show some aspects of the Qur’anic miracle by monitoring the most important means of text consistency and consistency through its application in the Holy Qur’an; planting conceptual rapprochement in the fields of discourse analysis between the old criticism (rhetoric) and the new (the linguistics of the text); And an attempt to explain the nature of the Qur’anic rhetorical images and how to operate them by inserting them into a general format and extracting the common structure between them. This research indicates that the Qur’an has included all witches. This is a clear and clear evidence of its comprehensiveness and the unity of its structure, even in terms of meaning, as it does not talk about a life without another. Also, the Qur’anic text is replete with many models, which the commentators mentioned in their books, which highlight their primacy in clarifying the tools of consistency and harmony in the Qur’anic text in general and in Surat Al-Baqarah in particular.